CMOEP regimen in the treatment of untreated peripheral T-cell lymphoma: a multicenter, single-arm, phase I study - Yu, Jingwei; Sun, Xiuhua; Gao, Guangxun; Yu, Li; Wang, Jiesong; Qiu, Lihua; Qian, Zhengzi; Li, Wei; Zhang, Huilai (Frontiers in Immunology, 2025)
The current first-line treatment for peripheral T-cell lymphoma (PTCL) has a typically poor prognosis. Developing a new regimen is urgently needed. This phase I study evaluated the maximum tolerated dose (MTD), safety, and efficacy of mitoxantrone hydrochloride liposome (Lipo-MIT) plus cyclophosphamide, vincristine, etoposide, and prednisone (COEP) in untreated PTCL. Patients with untreated PTCL were enrolled and received Lipo-MIT (15, 18, and 20 mg/m2) following a 3 + 3 dose-escalation design plus standard doses of COEP (750 mg/m2 cyclophosphamide, 1.4 mg/m2 vincristine, 60 mg/m2 etoposide, and 100 mg prednisone) every 3 weeks for 6 cycles. Primary endpoint was MTD; secondary endpoints were safety, overall response rate (ORR), complete response (CR) rate, progression-free survival (PFS), and overall survival (OS). As of the cut-off date (October 29, 2024), 13 patients received the Lipo-MIT plus COEP (CMOEP) regimen. No patients experienced dose-limiting toxicities (DLT); MTD was 20 mg/m2 and the recommended phase 2 dose was 18 mg/m2. Common ≥grade 3 hematologic toxicities included neutrophil count decreased (76.9%), white blood cell decreased (76.9%), and lymphocyte count decreased (46.2%). Most common ≥grade 3 non-hematologic toxicity was lung infection (15.4%). No deaths due to toxicities were reported. Among 12 patients evaluated for best response, ORR (95% CI, 73.5-100.0), and the CR rate was 66.7% (95% CI, 34.9-90.1). At a median follow-up of 8.5 months, the median PFS and OS were both not reached. The CMOEP regimen had a manageable safety profile and an encouraging clinical efficacy for PTCL patients, which warrants further investigation.Clinical trial registrationClinicalTrials.gov, identifier NCT05458180.